High bone mineral density in lifelong trained female team handball players and young elite football players - Hagman, M.; Helge, E. W.; Fristrup, B.; Joergensen, N. R.; Helge, J. W.; Krustrup, P. (European Journal of Applied Physiology, 2021)
Purpose: Low bone mineral density (BMD) and fractures are a major concern in the female population and preventative strategies are needed. Whether team sports participation may reduce age-related bone loss in elderly women is still uncertain. Methods: One hundred and thirty healthy, non-smoking women participated in this cross-sectional study, i.e., elderly (60-80 years) team handball players (EH, n = 35), elderly untrained controls (EC, n = 35), young (18-30 years) elite football players (YF, n = 30) and young untrained controls (YC, n = 30). A whole-body and two regional dual-energy X-ray absorptiometry (DXA) scans were performed to evaluate BMD and a blood sample was collected for measurement of bone turnover markers (BTMs). Results: EH had higher BMD in all regions of the lumbar spine, except for L1, compared to EC (8-10%), and higher BMD in the femoral Ward`s triangle (9%) and trochanter (7%) of the left leg. Furthermore, EH had higher mean leg BMD (8%) and whole-body BMD (5%) than EC. EH and YC had similar BMD in femoral trochanter, L1-L4 and mean leg despite an age difference of ~ 40 years. YF had higher BMD in all regions of the proximal femur (18-29%) and lumbar spine (12-16%) compared to YC, as well as higher mean leg BMD (20%) and whole-body BMD (13%). Sclerostin was 14% lower in EH compared to EC. YF showed higher PINP (98%), osteocalcin (57%), and CTX (83%) compared to YC. Conclusion: Lifelong team handball training and elite football training are associated with superior bone mineralization and changed bone turnover in elderly and young women.